Meningkatkan Hasil Belajar Siswa Melalui Penerapan Pembelajaran Kooperatif Tipe Think Pair-Share(TPS) - Bratanata Sanjaya; Mustika Wati; Syubhan An'nur (Berkala Ilmiah Pendidikan Fisika, 2013)
The low student’s achievement in physics is supposed because of the lack of variation in teacher learning model used. It has an impact on students' social skills. Their skills are lower and  the students tend to be passive. For that reasons the writer conducts this research and aims to improve student learning result through cooperative learning type TPS on the subject of elasticity and Hooke's law. The data analysis was used through descriptive, qualitative, and quantitative. The results of this research were: (1) teachers' skills in cycle I, II and III respectively 80,11%, 88,07%, and 96,59% are very good category (2) increase student's social skills each cycle in good category, (3) completeness student learning results in the classical also increased each cycle respectively 47,06%, 76,47%, and 97,06%, (4) student responses during the learning process is good categorized, for interest of 3,86 while the motivation by 3,94. It appears on result average for every statement in the good category. According to the results, it can be concluded that the student learning result of grade XI IPA 3 MAN 2 Model Banjarmasin at elasticity and Hooke's law subject are increasing after the application of cooperative learning model type TPS.